Bandwidth guaranteed multicast scheduling for virtual output queued packet switches - Pan, Deng; Yang, Yuanyuan (Journal of parallel and distributed computing, 2009)
Multicast enables efficient data transmission from one source to multiple destinations, and has been playing an important role in Internet multimedia applications. Although several multicast scheduling schemes for packet switches have been proposed in the literature, they usually aim to achieve only short multicast latency and high throughput without considering bandwidth guarantees. However, fair bandwidth allocation is critical for the quality of service (QoS) of the network, and is necessary to support multicast applications requiring guaranteed performance services, such as online audio and video streaming. This paper addresses the issue of bandwidth guaranteed multicast scheduling on virtual output queued (VOQ) switches. We propose the Credit based Multicast Fair scheduling (CMF) algorithm, which aims at achieving not only short multicast latency but also fair bandwidth allocation. CMF uses a credit based strategy to guarantee the reserved bandwidth of an input port on each output port of the switch. It keeps track of the difference between the reserved bandwidth and actually received bandwidth, and minimizes the difference to ensure fairness. Moreover, in order to fully utilize the multicast capability provided by the switch, CMF lets a multicast packet simultaneously send transmission requests to multiple output ports. In this way, a multicast packet has more chances to be delivered to multiple destination output ports in the same time slot and thus to achieve short multicast latency. Extensive simulations are conducted to evaluate the performance of CMF, and the results demonstrate that CMF achieves the two design goals: fair bandwidth allocation and short multicast latency.